Advanced oxidation and adsorptive bubble separation of dyes using MnO2-coated Fe3O4 nanocomposite - Kang, Yu-Gyeong; Yoon, Hakwon; Lee, Chung-Seop; Kim, Eun-Ju; Chang, Yoon-Seok (PERGAMON-ELSEVIER SCIENCE LTD, 2019)
In this study, MnO2-coated Fe3O4 nanocomposite (Fe3O4 @MnO2) was utilized to decompose H2O2 to remove dyes via advanced oxidation processes and adsorptive bubble separation (advanced ABS system). The combination of H2O2 and Fe3O4@MnO2 generated bubbles and formed a stable foam layer in the presence of a surfactant; sodium dodecyl sulfate (SDS) or cetyltrimethylammonium chloride (CTAC), separating dye from the solution. On the basis of radical quenching experiments, electron paramagnetic resonance and X-ray photoelectron spectroscopy analyses, it was confirmed that the MnO2 shell of catalyst was reduced to Mn(2)o(3) by H2O2, generating radicals and oxygen gas for the removal of dyes. In the advanced ABS system, .OH and O-1(2) were the main radical species and the O-2 concentrations of 0.34 and 0.71 mM were increased in the solution and headspace, respectively. The advanced ABS system demonstrated a high removal efficiency of methylene blue (MB) (99.0%) and the removal rate increased with increasing amounts of components (H2O2, catalyst and SDS). Also, the advanced ABS system maintained high removal efficiency of MB at a wide pH range of 3-9. In addition to the anionic surfactant of SDS, CTAC was applied as a cationic surfactant for the advanced ABS of anionic dyes. Lastly, the scale-up system was applied to remediate dye-contaminated river water and industrial wastewater for possible practical applications. (C) 2019 Elsevier Ltd. All rights reserved.
Keywords: SODIUM DODECYL-SULFATE; HYDROGEN-PEROXIDE DECOMPOSITION; SYNTHETIC WASTE-WATER; BIOLOGICAL TREATMENT; DEGRADATION; REMOVAL; MNO2; ACTIVATION; EFFICIENT; H2O2